INSTRUMEN KEUANGAN SYARI’AH DAN MERDEKA DARI RENTENIR - Sandra, Yopfie; Apriliantoni, Apriliantoni; Syadzili, Ahmad (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Islamic financial instruments were initially only considered as an alternative financial system. However, over time, these instruments have developed into one of the main factors that support economic growth, especially for the lower middle class and the poor. This has encouraged many investors to make Islamic financial instruments their primary choice. One of the significant contributions of Islamic financial instruments is to support inclusive and sustainable economic growth. Sharia-based investment patterns are able to encourage the development of the economic sector without increasing the number of people who are on the poverty line. Zakat and infaq, as an integral part of Islamic financial instruments, have been proven to play a role in distributing wealth to help people experiencing economic difficulties and support sustainable development. With the proper empowerment of Islamic financial instruments, the practices of loan sharks that harm the community can be minimized. Loan sharks often burden the poor with high-interest debt, which instead of helping them, worsens their economic condition. Through the Islamic financial system, the economy can be transformed into a more equitable, stable and inclusive one, so that the benefits are not only felt by the upper middle class, but also by all levels of society.